INTEGRATING VARIATION THEORY WITH MULTILINGUAL INSTRUCTION IN MULTILINGUAL CLASSROOMS: BRIDGING THEORY AND PRACTICE IN FOREIGN LANGUAGE ACQUISITION - Gomes, Nuno Miguel Alves dos Santos Teixeira; Correia, Ana Maria; Thota, Neena Jawaharlal (University of Saint Joseph, 2023)
This thesis explores language teaching and language acquisition by multilingual learners using a Variation Theory approach and multilingual teaching in a university setting in Macao, China. It includes three case studies applied to students of the Spanish language in the introductory level which took place from late August to early December of the year 2017. The first study describes Macao’s multilingual language learners in the University of Macao in 2017. Based on the LEAP-Q questionnaire, a questionnaire was created to inquire all Spanish language students about their languages´ background, their motivations to learn new languages, as well as their learning strategies. The second study shows how the usage of Variation Theory techniques and multilingual teaching techniques boosted the teaching and the learning during the semester. This study employs a case study methodology, by analysing in-class multiple interactions gathering information on how multilinguals´ language background affects the pedagogical process. It analyses a total of 28 classes of 1 hour and 15 minutes. The third study presents the analysis of a questionnaire to 82 students of the initial level of Spanish language in the University of Macao, along with the analysis of interviews from 10 selected multilingual students about their linguistic background and how they experienced the semester. These interviews collected more information about the effectiveness of the Variation Theory in the semester in terms of in-class teaching and learning. From the triangulation of these three studies, some conclusions have been drawn about the advantages of using Variation Theory and multilingual teaching techniques for multilingual students, for the language teacher and ultimately also into the curricular design of foreign language teaching. In sum, that the linguistic background of students plays a major role in how they acquire a new language and, that applying Variation Theory techniques can be an immensely effective technique in a language classroom setting; suggesting that multilingual students will gain from being previously identified and placed in a separate class where these variation techniques were applied. Since this thesis focuses solely on an introductory language course, there is ground to explore this same approach on more advanced multilingual language learners
Keywords: Foreign language teaching; Multilingualism; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph; Variation Theory

Set up and testing a secure cloud - Cheang, Son I. (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Information Technology (MIT); University of Saint Joseph

GROKYA: a privacy-friendly framework for ubiquitous computer - Farinha, Daniel Filipe G. (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Information Technology (MIT); University of Saint Joseph

Bowler plus: bowling ball feedback device - Leong, Chou Kin (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Information Technology (MIT); University of Saint Joseph

Developing a Holistic Approach to Learning and Teaching Introductory Object-Oriented Programming - Thota, Neena Jawaharlal (University of Saint Joseph, 2010)
This thesis articulates the development of a holistic approach to enhance learning and teaching in an object-oriented programming course. Starting with the premise that it is not possible to improve teaching without understanding how students learn programming, this thesis embodies the processes and reflections experienced while applying knowledge of how students learn programming, to design a learning environment that enhances learning outcomes. First, a theoretically based framework for the teaching of the course is developed. A holistic approach using a plurality of pedagogic theories, taxonomies, and instructional designs is employed to bridge the gaps between the bodies of knowledge relating to the ways that students approach programming and the application of this knowledge to design the course. Second, in two cycles of action research, the course is implemented and the analysis of its outcome is conducted using mixed methods data collection techniques. The evaluation is integrative and seeks multiple forms of evidence for student engagement and improved learning. The original contributions from this research in the form of new initiatives, perceptions, and understandings, as well as implications for theory and practice are described. A claim to knowledge is established by explaining the significance of the research to student learning, personal practice and beliefs, institutional influence, and potential for influence on computing education research. Quality criteria are applied to assess the validity and rigor of the action research project, and the research is appraised as a scholarly enquiry and a transformative process that led to innovative forms of thinking and acting
Keywords: Thesis and Dissertations PhD in Information System (D-IS); University of Saint Joseph